Cannabis cultivation in the world: heritages, trends and challenges - Pierre-Arnaud Chouvy (EchoGéo)
Despite cannabis being the most common illegal drug crop in the world and its worldwide presence, very little is known about its production, trade, and consumption at the global scale. This is due mostly to over a century of global prohibition and the dangers associated to researching illegal drug crop production. Worse, the limited data available about cannabis cultivation is most often inaccurate, unreliable, and highly controversial. While this has always been problematic, in terms of sheer knowledge and informed policy-making, it has now become even more acute of an issue as global trends towards decriminalisation and legalisation are already provoking negative unintended consequences in poor producing countries. This article is an effort to present the state of the current knowledge and the present and future stakes of the fast-changing cannabis industry and legislation.